2018
DOI: 10.1186/s13014-018-1136-5
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy based treatment for hepatocellular carcinoma with extensive portal vein tumor thrombosis

Abstract: BackgroundThere is currently no worldwide consensus for the management of hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT). We evaluated the efficacy of stereotactic body radiotherapy (SBRT) as the initial treatment for HCC with extensive PVTT based on a relatively large number of patients.MethodsIn our multidisciplinary approach for patients with hepatobiliary tumors, SBRT is recommended for unresectable HCC with PVTT or those with contraindication for transarterial chemoembolization (TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 31 publications
(35 reference statements)
3
50
0
2
Order By: Relevance
“…The results suggested that the ST group had a longer OS than the SA group. Shui et al [23] also reported that the ST group had a longer OS than the SA group (12.0 ± 1.6 vs. 3.0 ± 1.0 months, p < 0.001). Su et al [14] evaluated the long-term survival of the ST group and SA group in patients with large tumor sizes (> 5 cm), with a median tumor size of 8.5 cm.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results suggested that the ST group had a longer OS than the SA group. Shui et al [23] also reported that the ST group had a longer OS than the SA group (12.0 ± 1.6 vs. 3.0 ± 1.0 months, p < 0.001). Su et al [14] evaluated the long-term survival of the ST group and SA group in patients with large tumor sizes (> 5 cm), with a median tumor size of 8.5 cm.…”
Section: Discussionmentioning
confidence: 92%
“…Cai et al [13] showed that the combination of TACE and SBRT can avoid the limitations encountered when using TACE or SBRT alone and achieve a good ORR of 64%, which was significantly better than that of TACE alone (41.3%) or SBRT alone (33.3%). Shui et al [23] reported that the CR rate ranged from 9.7% at 3 months to 32.2% at 6 months after SBRT; the CR rate increased with time, and they found that most PD occurred within the first 3 months. A higher rate of CR and higher DCR may enhance the OS in the ST group.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, SBRT is still considered to be of therapeutic benefit for patients with PVT [31]. In the evaluable 53 cases of PVT, EndR was achieved in 42 cases (79.2%), which represented a higher percentage than in patients who received Sorafenib alone (7% based on mRECIST) in a comparable study [32].…”
Section: Discussionmentioning
confidence: 93%
“…As a result, in spite of the rapid development of radiotherapy for HCC, the efficacy was not significantly improved. In recent years, with the growth of stereotactic radiotherapy, SBRT is gradually appropriate for intermediate-to advanced-HCC [19][20][21][22] . SBRT delivers a high dose of radiation to HCC within a short period time and is effective and less invasive for the delivery of high radiation doses to the tumor with hypofractionation.…”
Section: Discussionmentioning
confidence: 99%